Students' Critical Thinking and Collaborative Skills Through the Problem-Based Collaborative Learning Model - Nisa, Ikmatul; Ardianik; Hatip, Ahmad (Jurusan Pendidikan Matematika FKIP Universitas Halu Oleo, 2025)
The implementation of the independent curriculum aims to maximize 21st-century skills, particularly in enhancing students’ critical thinking, collaboration, communication, and creativity. Critical thinking is the effort to prove the truth of knowledge based on facts. Collaboration skills are social skills that involve exchanging ideas, opinions, or concepts with others to reach solutions. This study aims to determine the effectiveness of the problem-based collaborative learning model on students’ critical thinking and collaborative skills in geometric transformation material. This study used a quasi-experimental type with a pretest-posttest control group design. The research sample consisted of 60 ninth-grade students at a private junior high school in Surabaya, divided into two groups, namely the experimental class and the control class. Data collection techniques included questions that tested critical thinking skills and collaborative skills questionnaires. Data analysis techniques included descriptive statistics and inferential statistics. The results of the study proved that (1) the problem-based collaborative learning model was effective in improving students' critical thinking skills with an average n-gain score of 79.3%, and (2) the problem-based collaborative learning model was quite effective in improving collaborative skills with an average n-gain score of 72.3%.